Mediation effect of partnership on procurement strategy factors influencing sustainable smart housing development, Nigeria. Issue 3 (20th October 2020) - Musonda, Innocent; Gambo, Nuru
Abstract : Purpose: The procurement strategy challenges that influence the development of sustainable smart housing require a holistic system approach that models the relationships between procurement strategies and sustainable smart housing development approach. This considers the use of technology partnering to ensure value for money. The purpose of the paper is to assess the mediation effect of the technology partnership on procurement strategy influencing sustainable smart housing development. Design/methodology/approach: This study used a quantitative approach and primary data were collected via a structured questionnaire. In total, 500 survey questionnaires were administered to project managers in the Nigerian construction industry and a stratified proportionate random sampling method was used for the selection of respondents. Findings: The results indicated that the procurement strategy influenced sustainable smart housing development in Nigeria, and the technology partnership mediates the relationship between procurement strategy and sustainable smart housing development. Research limitations/implications: This quantitative study is based on the perception of construction project managers in Nigeria. The findings serve as an awareness of the government and other stakeholders in the construction industry on the development of sustainable smart housing in Nigeria. Practical implications: The study establishes that technology partnership mediates the relationship between procurement strategy factors and sustainable smart housing development through enhancement of smart housing development and serves as awareness to stakeholders on the factors influencing smart housing development in Nigeria. Social implications: The study suggests that technology partnership influences the effect of procurement strategy factors on sustainable smart housing and hence improves the development of smart housing in developing countries. Originality/value: Mediation roles of technology partnership minimize procurement strategy challenges and enhance sustainable smart housing development.